A New Method of Scalable Image Compression Coding - Yang, Yan (Applied Mechanics and Materials, 2013)
This paper presents a new method of scalable image compression coding based on the wavelet transform. This method delimits the region of interest of the original image, and give a high-quality encoding to this region and a rough encoding to the rest. The result shows that in the limited memory space, this algorithm provides the coarser reconstruct image to satisfy the basal subject quality. Using this method, we can give a high quality encoding to the region for interest.